Analysis of Female Character “Prof. Mc Gonagall” in Breaking Women Stereotypes in Harry Potter Movies - Falaily , Irma Putri; Dewi , Maya Kurnia (Praniti: Jurnal Pendidikan, Bahasa, dan Sastra, 2023)
This research analyzes all the Harry Potter films series using feminist theory, especially liberal feminism. This research aims to determine the feminist character of Prof. Mc Gonagal and what is the character of Prof. Mc Gonagal and changing female stereotypes in the Harry Potter films. This research uses a qualitative method, where the author provides several notes in dialogue that discuss several reasons and factors of Prof. McGonagal's feminist character. The results of this research show that the character possessed by Prof. McGonagal shows that she is a feminist character. Some dialogue evidence shows that Prof. McGonagall has a feminist character. With the character that Prof. Mc Gonagall was also able to change stereotypes about women. In the film there is also a depiction of a female character who is the opposite of Prof. Minerva McGonagall. Where the depiction is made into a character who tends to be weak and obedient to men.